A novel NCI‐H69V small cell lung cancer functional mini‐tumor model for future treatment screening applications. (7th April 2022) - van der Merwe, Liezaan; Svitina, Hanna; Willers, Clarissa; Wrzesinski, Krzysztof; Gouws, Chrisna
Abstract: Small cell lung cancer (SCLC) is aggressive and despite multiple clinical trials, its standard of care is unchanged for the past three decades. In vitro cancer models are crucial in chemotherapy development, and three‐dimensional (3D) models aim to bridge the gap between two‐dimensional (2D) flat cultures and in vivo testing. Functional 3D spheroids can better represent the in vivo situation and tumor characteristics than 2D models. An NCI‐H69V SCLC mini‐tumor model was developed in a clinostat‐based rotating bioreactor system. Spheroid growth and viability were characterized for 30 days, and the ideal experimental window with mature and metabolically stable spheroids was determined. Application of the model for anticancer treatment screening was validated with the standard chemotherapeutic drug irinotecan, for an exposure period of 72 h. The following parameters were measured: soluble protein content, planar surface area measurements, intracellular adenosine triphosphate and extracellular adenylate kinase levels, and glucose consumption. Histological morphology of the spheroids was observed. The established model proved viable and stable, while treatment with irinotecan caused a decrease in cell growth, viability, and glucose consumption demonstrating reactivity of the model to chemotherapy. Therefore, this NCI‐H69V SCLC functional spheroid model could be used for future anticancer compound screening.